Function of AP2/ERF Transcription Factors Involved in the Regulation of Specialized Metabolism in Ophiorrhiza pumila Revealed by Transcriptomics and Metabolomics - Udomsom, Nirin; Rai, Amit; Suzuki, Hideyuki; Okuyama, Jun; Imai, Ryosuke; Mori, Tetsuya; Nakabayashi, Ryo; Saito, Kazuki; Yamazaki, Mami (Frontiers in Plant Science, 2016)
The hairy roots (HR) of Ophiorrhiza pumila produce camptothecin (CPT), a monoterpenoid indole alkaloid used as a precursor in the synthesis of chemotherapeutic drugs. O. pumila HR culture is considered as a promising alternative source of CPT, however, the knowledge about the biosynthetic pathway and regulatory mechanism is still limited. In this study, five genes that encode AP2/ERF transcription factors, namely OpERF1 to OpERF5, were isolated from HR of O. pumila. Phylogenetic analysis of AP2/ERF protein sequences suggested the close evolutionary relationship of OpERF1 with stress-responsive ERF factors in Arabidopsis and of OpERF2 with ERF factors reported to regulate alkaloid production, such as ORCA3 in Catharanthus roseus, NIC2 locus ERFs in tobacco, and JRE4 in tomato. We generated the transgenic HR lines of O. pumila, ERF1i and ERF2i, in which the expression of OpERF1 and OpERF2, respectively, was suppressed using RNA interference technique. The transcriptome and metabolome of these suppressed HR were analyzed for functional characterization of OpERF1 and OpERF2. Although significant changes were not observed in the metabolome, including CPT and related compounds, the suppression of OpERF2 resulted in reduced expression of genes in the 2-C-methyl- D -erythritol 4-phosphate and secologanin-strictosidine pathways, which supply a precursor, strictosidine, for CPT biosynthesis. Furthermore, while it was not conclusive for OpERF1, enrichment analysis of differentially expressed genes in the suppressed HR showed that the gene ontology terms for oxidation-reduction, presumably involved in secondary metabolite pathways, were enriched in the ERF2i downregulated gene set. These results suggest a positive role of OpERF2 in regulating specialized metabolism in O. pumila.